Examining the role of affordability, citizen engagement, and social solidarity in determining health insurance coverage in Kenya - Maritim, Beryl Chelangat (University of the Witwatersrand, Johannesburg, 2023)
Rationale: Healthcare costs cause severe financial hardship globally and many low-and middle-income countries (LMIC) are turning to social health insurance to provide financial risk protection and increase population coverage. However social health insurance schemes in LMICs experience significant growth challenges owing to difficulties reaching informal workers through contributory health insurance systems. Kenya has undertaken several health sector reforms and efforts to increase health insurance coverage but has had limited success in capturing the large proportion of informal workers. The broad aim of this study was to describe and assess the reasons for low enrolment in the national insurance scheme among the Kenyan informal worker households in Bunyala sub-County, Busia County, Kenya. It focused on the role of affordability of premiums, citizen engagement and social solidarity in NHIF coverage among the informal worker households. Methods: This study employed an explanatory mixed methods study approach with quantitative and qualitative primary data collection. The quantitative phase included a household survey (n=1,773) from which 36 respondents were purposively identified to participate in in-depth household interviews. The study also conducted 6 focus group discussions (FGD) groups with community stakeholders, and 11 key informant interviews with policymakers and implementers at national and sub-national level. Quantitative data was analyzed using R while qualitative data was analyzed thematically using both manual methods and NVIVO software. Results: Only 12% of households reported having health insurance and NHIF was unaffordable for the majority of households, both insured (60%) and uninsured (80%). Rural households spent a significant proportion (an average of 12%) of their household budget on out of pocket (OOP) expenses on health care, with both insured and uninsured households reporting high OOP spending and similar levels of impoverishment due to OOP I found that there was high awareness of NHIF but low levels of knowledge on services, feedback and accountability mechanisms. Barely half (48%) of the insured were satisfied with the NHIF benefit package. Nearly all of the respondents (93%) were unaware of mechanisms to reach NHIF for feedback or complaints. Respondents expressed desire to know the NHIF performance but expressed high levels of mistrust in the fund owing to negative reports on NHIF performance in the media. This study found high willingness to prepay for healthcare among those without insurance (87.1%) with competing priorities, low incomes, poor access and quality of health services, lack of awareness of flexible payment options cited as barriers to enrolment. More than half of respondents expressed willingness to tolerate risk and income cross-subsidization suggesting strong social solidarity, which increased with socio-economic status. Participants expressed concerns about value of health insurance given its cost, availability and quality of services, and financial protection relative to other social and economic household needs. Households resorted to borrowing, fundraising, taking short term loans and selling family assets to meet healthcare costs. Implications: This study provides a nuanced insight into the challenges of increasing coverage among rural informal worker households with considerations for rolling out mandatory NHIF membership. The findings imply that majority of the informal worker households in rural areas need assistance to afford NHIF. These study findings also highlight the importance of fostering and leveraging existing social solidarity to move away from flat rate contributions and apply more progressive contribution that allow for fairer risk and income cross-subsidization. Finally, the government should rapidly scale up the indigent program to cover most rural informal worker households. There is also need to invest in robust strategies to effectively identify subsidy beneficiaries. Significant reforms of NHIF and health system are required to provide adequate health services and financial risk protection for rural informal households in Kenya. NHIF also needs to evaluate their citizen engagement and accountability frameworks to increase awareness, member satisfaction, improve state accountability to citizens and incorporate citizen voice in their processes.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Informal Workers; NHIF; Social health Insurance; Universal coverage; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education